PENGARUH PUPUK NPK DAN NANO PESTISIDA SERAIWANGI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN CABAI MERAH (Capsicum annuum L.) - Milda Ernita; Alhidayati Alhidayati; Widodo Haryoko (Percetakan Umi Toaha Makassar, 2020)
Experiments on the influence of NPK fertilizers and citronella pesticides nano on the growth and yield of red chili (Capsimum annuum L.) were carried out on dry land in Korong Pasar Baru village, Nansabaris District, Padang Pariaman Regency, West Sumatra from February - June 2020. The research objective was to determine the interaction of NPK fertilizer and citronella pesticide on growth, yield and disease attack rates in red chilies. The experiment used a randomized block design (RBD) with two factors. The first factor was the dosage of NPK fertilizer consisting of 3 levels, namely: 0 kg/ha, 100 kg/ha, and 150 kg/ha. The second factor is the concentration of citronella pesticide nano, namely: 0 ml/L, 3 ml/L, 6 ml/L and 9 ml/L. Based on the results of the experiment, it can be concluded that NPK fertilizers and citronella pesticides can increase the growth and yield of chili plants and suppress curly disease 83.4%.